A Random Matrix Approach to Absorption in Free Products. (7th August 2020) - Hayes, Ben; Jekel, David; Nelson, Brent; Sinclair, Thomas
Abstract: This paper gives a free entropy theoretic perspective on amenable absorption results for free products of tracial von Neumann algebras. In particular, we give the 1st free entropy proof of Popa's famous result that the generator MASA in a free group factor is maximal amenable, and we partially recover Houdayer's results on amenable absorption and Gamma stability. Moreover, we give a unified approach to all these results using 1 -bounded entropy. We show that if M = P * Q, then P absorbs any subalgebra of M that intersects it diffusely and that has 1 -bounded entropy zero (which includes amenable and property Gamma algebras as well as many others). In fact, for a subalgebra P ≤M to have this absorption property, it suffices for M to admit random matrix models that have exponential concentration of measure and that "simulate" the conditional expectation onto P .